2004
DOI: 10.1074/jbc.m306183200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cathepsin B as a Mediator of Neuronal Death Induced by Aβ-activated Microglial Cells Using a Functional Genomics Approach

Abstract: Alzheimer's disease is a progressive neurodegenerative disease characterized by senile plaques, neurofibrillary tangles, dystrophic neurites, and reactive glial cells. Activated microglia are found to be intimately associated with senile plaques and may play a central role in mediating chronic inflammatory conditions in Alzheimer's disease. Activation of cultured murine microglial BV2 cells by freshly sonicated A␤42 results in the secretion of neurotoxic factors that kill primary cultured neurons. To understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 54 publications
4
97
1
Order By: Relevance
“…Additionally, we revealed that extracellular cathepsin D in the conditioned medium of U18666A-treated cultures can trigger degeneration in naive neuronal cultures and that removing the enzyme from the conditioned medium using agarose beads coupled to cathepsin D antibodies prevented neuronal death. Thus, extracellular cathepsin D secreted from U18666A-treated neurons can induce toxicity in a manner similar to that reported for cathepsin B, which is secreted following A␤-mediated activation of microglia (84). This is further validated by the observation that exogenous cathepsin D can trigger degeneration of hippocampal cultured neurons in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, we revealed that extracellular cathepsin D in the conditioned medium of U18666A-treated cultures can trigger degeneration in naive neuronal cultures and that removing the enzyme from the conditioned medium using agarose beads coupled to cathepsin D antibodies prevented neuronal death. Thus, extracellular cathepsin D secreted from U18666A-treated neurons can induce toxicity in a manner similar to that reported for cathepsin B, which is secreted following A␤-mediated activation of microglia (84). This is further validated by the observation that exogenous cathepsin D can trigger degeneration of hippocampal cultured neurons in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 60%
“…Changes in the transcriptional profile of primary rodent microglia in different conditions, such as after exposure to IFN-γ , TGF-β (Paglinawan et al, 2003) or colony-stimulating factors (Re et al, 2002), have been described. For inflammatory stimulation, data can be found for human microglia (Walker et al, 2001) or the murine BV-2 (Gan et al, 2004) cell line exdata were directly compared to some data from PM to add credibility. Studies with primary microglia usually involve the use of antibiotics, at least for some time, although it is known that these can influence the outcome of experiments (Kuhlmann, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last several years, we have seen a revolution in highthroughput expression profiling of diseased human brain tissue (Ginsberg et al, 2000;Ho et al, 2001;Loring et al, 2001;Colangelo et al, 2002;Mufson et al, 2002;Yao et al, 2003;Blalock et al, 2004) and various models of human brain disorders (Dickey et al, 2003(Dickey et al, , 2004Marcotte et al, 2003;Mirnics et al, 2003;Gan et al, 2004;Wang et al, 2004). Although the expression profiling of AD tissue continues to generate data of enormous potential, the interpretation of the postmortem findings is greatly complicated by the nature of AD disease progress (Mirnics et al, 2001a;Marcotte et al, 2003;Mirnics and Pevsner, 2004).…”
Section: Introductionmentioning
confidence: 99%